Withstanding Persecution as a Corroboration of Legitimacy in the New Testament: Reflections on the Resulting Ethical and Hermeneutical Quandary - Kelhoffer, James A. (Dialog, 2011)
Assertions of standing, authority, and power claimed on the basis of withstanding persecution play a prominent and heretofore under-appreciated role in much of the New Testament literature. Yet deriving legitimacy from persecution presents an interpretive quandary not unlike those inherited from biblical passages that condone slavery or unhealthy attitudes toward women and men. Reflection on how we construe ourselves in relation to suffering is an agendum inadequately realized in the New Testament that commends itself for twenty-first century ethics and theology.